An optimal solution for managing the deformation behaviour of engineering structures - Halim Setan, 1957- 549392; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Sains dan Geoinformasi 513246; Universiti Teknologi Malaysia. Pusat Pengurusan Penyelidikan 520 (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL